The Universal Protection of Human Rights - Dóra Szikszai, Laura Kovács-Berényi; Kovács, Péter; Béres, Nóra (2026)
'The Universal Protection of Human Rights' gives a historical overview of the evolution of the concept of human rights and presents the standard setting and monitoring activities within the so called sectorial protection of human rights, secured by different UN conventions concerning the fight against different forms of discrimination or the protection of vulnerable communities. A special emphasis is put on the legislative implementation of these rights in Central European countries and the confrontation between the abstract legal framework and individual cases as reflected in the activity of the monitoring bodies of the conventions adopted under the auspices of the United Nations.